(untitled) (Jurnal Geomine, 2019)
One of the important things to conduct in mining business is mine drainage. The aim of this research was to measure runoff water discharge which entered Sump, find out the area of the catchment area and calculate the pump outlet discharge. The research method used direct observation in field including trench area and pipe diameter. Water in sump had to be able to be taken out from mine so it would be dry. The result of actual pump discharge was 227 liter/sec or 0.227 m3/sec, 817.2 m3/hour with sup volume 4.269.344 m3. wide trenches was 3.992 m2, pump used was multiflo 420EX pump with type of HDPE pump (High Density Polytethylene) with diameter 14 inch and pump length of 1500 m. Mine drainage used in pit A mine dewatering included trench (open channel) and sump, water which entered in location of miners was runoff water. runoff water in miner was 3.469,28 m3/hour, catchment area from was 683.71 Ha included base pit area and range 595.88 Ha and rehab 87.83 Ha.